2021
DOI: 10.1039/d1fo01147b
|View full text |Cite
|
Sign up to set email alerts
|

Fructooligosaccharide supplementation alleviated the pathological immune response and prevented the impairment of intestinal barrier in DSS-induced acute colitis mice

Abstract: The dysbiosis of gut microbiota is closely related to the occurrence and development of inflammatory bowel disease (IBD). The manipulation of intestinal flora through prebiotics or probiotics is expected to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 48 publications
(52 reference statements)
0
20
0
Order By: Relevance
“…42 And in Minjing Liao et al 's study, both FOS and synbiotic increased the expression of mucomucin (MUC2) and epithelial tight junction proteins (ZO-1, occludin, claudin-1). 43…”
Section: The Application Of Different Kinds Of Functional Oligosaccha...mentioning
confidence: 99%
See 2 more Smart Citations
“…42 And in Minjing Liao et al 's study, both FOS and synbiotic increased the expression of mucomucin (MUC2) and epithelial tight junction proteins (ZO-1, occludin, claudin-1). 43…”
Section: The Application Of Different Kinds Of Functional Oligosaccha...mentioning
confidence: 99%
“…42 Another study, conducted by Minjing Liao et al, separately verified the roles of FOS and synbiotic proteins in alleviating DSSinduced colitis and found that both decreased the expression of IL-6 and TNF-α, increased the expression of T-BOX21 (T-BOX21 can regulate TNF-α production in colonic dendritic cells and is thought to control the occurrence of pro-inflammatory responses on mucosal surfaces) and IL-10, partially attenuated the DSS-induced decline in diversity in the gut microbiota, increased the abundance of anti-inflammatory bacteria (e.g., Faecalibaculum and Bifidobacterium) and decreased the abundance of pro-inflammatory bacteria (e.g., Mucispirillum). 43 FOS also play an important role in repairing intestinal barrier damage caused by inflammation. The experiments con-ducted by Fermín Capitán-Cañadas et al confirmed that FOS not only increased the expression of occludin, but also reduced the invasion of intestinal epithelial cells by inflammation.…”
Section: Fructo Oligosaccharides (Fos)mentioning
confidence: 99%
See 1 more Smart Citation
“…Prebiotics are indigestible food ingredients that improve the gut microbiota structure by providing carbon sources, making metabolic substrates available for the gut microbiota to utilize, and adjusting the gut microenvironment, such as in terms of pH value, gastrointestinal absorption, and enzyme hydrolysis ( 173 , 174 ). Fructo-oligosaccharide (FOS) is a well-studied effective prebiotic consisting of one glucose and one fructose, and it has shown multiple beneficial effects in several animal models including the following: (a) resisting bacterial infection such as that of enterotoxigenic E. coli ( 176 ), (b) promoting the colonization of probiotics like Bifidobacterium and Lactobacillus ( 177 180 ), (c) increasing the production of SCFAs by the use of these probiotics ( 180 ), and (d) downregulating the pro-inflammatory cytokine expression and protecting the mucosal barrier ( 181 ). Besides FOS, inulin, galacto-oligosaccharides, and some foods containing indigestible β-glucans such as termites, a kind of Chinese traditional medicine, also have a similar effect ( 174 ).…”
Section: Prospects Of Interventions Targeting Glucose Metabolism Glyc...mentioning
confidence: 99%
“…28,29 Although a study published in 2021 reported anti-inflammatory effects of FOS in DSS-induced model, the dose of oral administration is too high (2 g per kg body weight per day). 30 In contrast, anti-inflammatory activities of butyrate have been confirmed but its effect on gut microbiota is limited and still needs further validation. 31 In addition, butyrate is generally considered as a safe food additive for health maintenance and chronic disease treatment.…”
Section: Introductionmentioning
confidence: 99%